Bai Mancooverbai Ardon Pyaav - Ghosh, Ayan (2023)
Located under the shade of a Banyan Tree, Bai Mancooverbai Ardon Pyaav was the site of an important freshwater well in the erstwhile Bombay Green area before it was converted to a drinking fountain in 1873.